Viability of Pentadesma in reduced habitat ecosystems within two climatic regions with fruit harvesting - Maria C. A. Leite; Benito Chen-Charpentier; Folashade B. Agusto; Orou G. Gaoue; Natali Hritonenko (Journal of Biological Dynamics, 2022)
Habitat loss and harvesting of non-timber forest products (NTFPs) significantly affect the population dynamics. In this paper, we propose a general mathematical modelling approach incorporating the impact of habitat size reduction and non-lethal harvesting of NTFP on population dynamics. The model framework integrates experimental data of Pentadesma butyracea in Benin. This framework allows us to determine the rational non-lethal harvesting level and habitat size to ensure the stability of the plant ecosystem, and to study the impacts of distinct levels of humidity. We suggest non-lethal harvesting policies that maximize the economic benefit for local populations.